Dislocation generated by electron irradiation - -, Suryanto (Trans Tech Publications, Switzerland, 2012)
Dislocation loop was generated by electron irradiation in nickel aluminum alloy. It is important to know dislocation characteristics obtained from a high energetic electron irradiation. If b is the Burger vector of a dislocation loop and g is the diffraction vector, dislocation loop will appear larger, smaller or disappear for g.b>0, g.b<0 or g.b=0, respectively. Dislocation loop was determined as follows – first, the appearance of dislocation loops is arranged in observation table. Second, based on type of dislocation loop, Burger vector and diffraction vector, appearance of dislocation loop is arranged in calculation table. Third, based on observation and calculation table, Burger vector and type of dislocation loop is determined. The results show that dislocation loops consist of perfect dislocation loops and Frank dislocation loops. The perfect dislocation loops have Burger vectors of ½[0 ] and ½[ 0] while Frank dislocation loops have Burger vectors of ⅓[1 1], ⅓[11 ], ⅓[ 11], ⅓[111], ⅓[1 1], ⅓[11 ] and ⅓[ 11]. All dislocation loops are interstitial types.